A distributed approach to surround sound production - Smith, Adrian Wilfrid (Rhodes University, Faculty of Science, Department of Computer Science, 1999)
The requirement for multi-channel surround sound in audio production applications is growing rapidly. Audio processing in these applications can be costly, particularly in multi-channel systems. A distributed approach is proposed for the development of a realtime spatialization system for surround sound music production, using Ambisonic surround sound methods. The latency in the system is analyzed, with a focus on the audio processing and network delays, in order to ascertain the feasibility of an enhanced, distributed real-time spatialization system.
Keywords: Surround-sound systems; Computer sound processing; Music -- Data processing